Development of antimicrobial resistance due to the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) (Research, Society and Development, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a new coronavirus identified in 2019. This disease, which may cause a serious respiratory infection, has been designated an international public health emergency and is being treated with several types of antivirals, antibiotics, and antifungals. While society works hard to combat the coronavirus disease 2019 (COVID-19) pandemic, it is equally vital to be prepared for the outbreak’s notorious effects on the development of antimicrobial resistance (AMR). Antibiotic misuse and overuse are predicted to have serious ramifications for antibiotic stewardship programs and AMR management worldwide. Importantly, the global influence on the creation of novel antimicrobial resistance is uncertain due to a paucity of data on antimicrobial usage during the COVID-19 pandemic. The current pandemic might be a useful tool for depicting the spread of antimicrobial resistance and underlining the difficulties in managing the issue once it has emerged. This review aims to assess available data on bacterial infections in coronavirus-infected patients and to offer insight into the development of AMR in the face of the current public health issue.